Micro Enterprises Performances Potential Index (MEPPI): A Study with the Reference to Rural Areas of the Cuddalore District, Tamilnadu - R. Pazhanisamy; E. Selvarajan (ZBW – Leibniz Information Centre for Economics, 2019)
Micro enterprises are recognized as the prime source of livelihood for the poor population in the rural areas around the globe. The impact of micro enterprises on the rural economy is determined by the performance of these micro enterprises, their success rate and the potential for the sustainability in the market which depends upon the various factors like financial capability, profitability, resource availability, demand in the market, skill up gradation of the micro entrepreneurs and the competitiveness. In addition to this the factors such as labour, the performance potential of the micro enterprises, capital availability with low cost technology, raw materials availability, better infrastructure, political stability and the supportive economics policies like subsidies and export import guidance and many others join together to determine the performance and sustainability of the micro enterprises. A successful entrepreneur needs to be known and ready to adopt the necessary changes and differentiations in the product suitable to the market change which warrants the entrepreneurs knowledge about the dynamics of the market conditions regarding the trend in the demand, demand forecasting, performance evaluation of the enterprises at the particular period and its production and market potential for the future. The available literature about the performance of micro enterprises reveals that lake of timely assessment about the concurrent performance of the micro enterprise and their performance potential for the future leads to the failure of the products and the microenterprises (Olawale (2014), Wan Nurulasiah binti Wan Mustapa, Abdullah Al Mamun , Mohamed Dahlan Ibrahim, Mbugua Stephen Kamunge , Agnes Njeru , Ondabu Ibrahim Tirimba, (2018) and Bushu 2019) which calls for an in-depth attempt to discover the resource and market potential for the best performance of the micro enterprises at the gross root level. This paper is attempted to fill this gap in research.
Additional information: Revised Version
Keywords: D21; D47; G24; H43; L22; L26; 330; Micro Enterprises Performance Index; Potential Performance Index; Rural Micro Enterprises; Sustainability of Micro Enterprises; Challenges of Micro Enterprises